The Effect of E-Money, Economic Literacy and Parents' Income on Consumptive Behavior (Universitas Negeri Semarang, 2022)
This study aimed to analyze the effect of e-money, economic literacy and parental income on the consumptive behavior of the students of the Faculty of Economics, UNP. This type of research was quantitative research with a descriptive approach. Data collection techniques used questionnaires, tests, and documentation. The sampling technique in this study was purposive sampling with a total sample of 133 respondents. The data analysis technique used multiple linear regression analysis. The results of this study indicated that: (1) e-money had a positive and significant effect on the consumptive behavior of FE UNP students, (2) economic literacy had a negative and significant effect on the consumptive behavior of FE UNP students, (3) parents' income had a positive and significant effect on the consumptive behavior of students. FE UNP,